Determining Influenza Virus Shedding at Different Time Points in Madin-Darby Canine Kidney Cell Line - Asghar Abdoli; Hoorieh Soleimanjahi; Masoumeh Tavassoti Kheiri; Abbas Jamali; Azam Jamaati (Cell Journal, 2013)
Objective: Monitoring of influenza virus shedding and optimization of multiplicities of infection (MOI) is important in the investigation of a virus one step growth cycle and for obtaining a high yield of virus in vaccine development and conventional basic diagnostic methods. However, eluted infectious viruses may still be present immediately after virus inoculation and when cells are washed following virus cultivation which may lead to a false positive virus infectivity assay.Materials and Methods: In this experimental study, we investigated influenza virus progeny production in Madin-Darby canine kidney (MDCK) cells with five different MOI at determined time points. The results were analyzed by end point titration tests and immunofluorescence assay.Results: Higher titers of eluted virus were observed following a high MOI inoculation of virus in cell culture. Most probably, this was the result of sialic acid residues from viral hemagglutin in proteins that were cleaved by neuraminidase glycoproteins on the surface of the influenza virus, which promoted viral spread from the host cell to the culture supernatant or during endocytosis, where viruses recycle to the cell surface by recycling endosomes which culminated in virus shedding without replication.Conclusion: We demonstrated that the pattern of influenza virus progeny production was dose-dependent and not uniform. This production was influenced by several factors, particularly MOI. Understanding the exact features of viral particle propagation has a major impact in producing high virus yields in the development of vaccines. Use of lower MOI (0.01) could result in accurate, precise quantitative assays in virus diagnosis and titration methods.